Chemical composition, rumen fermentation kinetics, digestibility and energy value of cassava leaves hay at different storage times - Beelen, Patricia M. Guimaraes [UNESP]; Santos, D. F. [UNESP]; Amorim, P. L. [UNESP]; Paula, T. A. [UNESP]; Beelen, R. N. [UNESP]; Fraga, A. B. [UNESP]; Teixeira, I. A. M. A. [UNESP]; Lira Junior, W. B. [UNESP] (Int Buffalo Information Ctr, 2013)
Cassava leaves have been widely used as a protein source for ruminants in the tropics. However, these leaves contain high level of hydro-cyanic acid (HCN) and condensed tannins (CT). There are evidences that making hay can eliminate more than 90% of HCN and that long-term storage can reduce CT levels. A complete randomized design with four replicates was conducted to determine the effect of different storage times (0-control, 60, 90 and 120 days) on chemical composition, in vitro rumen fermentation kinetics, digestibility and energy value of cassava leaves hay. Treatments were compared by analyzing variables using the GLM procedure (SAS 9.1, SAS Institute, Inc., Cary, NC). Crude protein (CP) and ether extract (EE) of the cassava hay were not affected (P > 0.05) by storage time (17.7% and 3.0%, respectively). Neutral detergent fiber, acid detergent fiber, total carbohydrate and non-fiber carbohydrate were not affected either (P>0.05) by storage time (47.5, 32.6, 72.3 and 25.8% respectively). However, other parameters were influenced. CT was lower (P<0.05) in hay after 120 days of storage compared with control (1.75% versus 3.75%, respectively). Lignin and insoluble nitrogen in neutral detergent, analyzed without sodium sulfite, were higher (P<0.01) after 120 days of storage, compared with the control (11.22 versus 13.57 and 1.65 versus 3.81% respectively). This suggests that the CT has bound to the fiber or CP and became inactive. Consequently, the in vitro digestibility of organic matter (50.36%), total digestible nutrients (44.79%) and energy (1.61 Mcal/KgMS), obtained from gas production data at 72 h of incubation, has increased (P<0.05) with storage times (56.83%, 51.53% and 1.86 Mcal/KgMS, respectively). The chemical composition and fermentative characteristics of cassava hay suffered variations during the storage period. The best values were obtained after 90 days of storage. This is probably due to the reduction in condensed tannins.
Keywords: By products; Manihot esculenta; Proanthocyanin